Identification of the Relationship between Oil Body Morphology and Oil Content by Microstructure Comparison Combining with QTL Analysis in Brassica napus - Gu, Jianwei; Chao, Hongbo; Wang, Hao; Li, Yonghong; Li, Dianrong; Xiang, Jun; Gan, Jianping; Lu, Guangyuan; Zhang, Xuekun; Long, Yan; Li, Maoteng (Frontiers in Plant Science, 2017)
Abstract Oil bodies (OBs) are relatively simple but very important organelles comprising a matrix of triacylglycerol (TAG) surrounded by a phospholipid monolayer embedded and covered with unique proteins. The OB structure in B. napus with different oil content and the relationship between the oil content and the OB structure needs to be better understood. In this paper, the characteristics of OBs in the embryo of a series of B. napus materials with different oil content ranging from 34% to over 60% were studied. The results indicated that the OB size was significantly positively correlated with the oil content but was significantly negatively correlated with the glucosinolates and the protein content. Many genes associated with TAG synthesis, OB-membrane proteins and the cell progress regulatory pathway were identified in the confidence interval of co-located QTLs for oil content, fatty acid (FA) compositions and protein content. Our results suggested that the morphology of OBs might be directly controlled by the genes associated with OB-membrane proteins and indirectly controlled by the genes associated with TAG synthesis and cell progress regulatory pathway.